Review of passive drag reduction techniques for bluff road vehicles. - Altaf, Alaman; Omar, Ashraf Ali; Asrar, Waqar (IIUM Press, 2014)
This paper presents a review of the techniques used to reduce aerodynamic drag over bluff bodies such as cylinders, spheres, 2D bodies with blunt backs and their application to commercial road vehicles. The recent research carried out on the drag reduction is presented and categorised. A new classification of the techniques is introduced and major contributions under them are shown. It can be concluded that there is not much work done with realistic 3D bluff bodies, especially using passive methods.